2015
DOI: 10.1186/s13018-015-0319-0
|View full text |Cite
|
Sign up to set email alerts
|

Shoe heel abrasion and its possible biomechanical cause: a transversal study with infantry recruits

Abstract: BackgroundExcessive shoe heel abrasion is of concern to patients and shoe manufacturers, but little scientific information is available about this feature and its possible causes. The purpose of this study was to relate this phenomenon with biomechanical factors that could predispose to shoe heel abrasion.MethodsNinety-seven recruits (median age 25) were enrolled in this study. Shoe abrasion was assessed manually with a metric plastic tape on the posterior part of the heel that comes in contact with the ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…For medial abrasion and centro-medial abrasion (i.e., inwardly slanted shoe abrasion) among them, in particular, it has been found that abrasion patterns that are inwardly skewed on both feet are very rare. This was similar to the results of a study by Baumfeld et al [5], who measured 47.1% lateral abrasion and 4.7% medial abrasion in 97 infantrymen. Additionally, the total number of subjects with different forms of abrasion on both feet was 18, accounting for only 6.1% of the total number of participants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For medial abrasion and centro-medial abrasion (i.e., inwardly slanted shoe abrasion) among them, in particular, it has been found that abrasion patterns that are inwardly skewed on both feet are very rare. This was similar to the results of a study by Baumfeld et al [5], who measured 47.1% lateral abrasion and 4.7% medial abrasion in 97 infantrymen. Additionally, the total number of subjects with different forms of abrasion on both feet was 18, accounting for only 6.1% of the total number of participants.…”
Section: Discussionsupporting
confidence: 92%
“…Participants brought their worn-out shoes to analyze the abrasion of the shoes according to the human body dimensions and gait characteristics of the participants. After checking the abrasion on the soles, the abrasion of the shoes was classified into five types by referring to the study of Baumfeld et al [5]. Table 2 shows that the heel is divided into medial, central, and lateral parts to define five types of shoe abrasion.…”
Section: Collecting and Classifying Shoe Abrasion Typesmentioning
confidence: 99%
“…Among the visually prominent variables in the results of Koreans’ walking characteristics, the main variable appears to be how far forward they bend and walk. The shapes of one’s neck and spine vary from individual to individual [ 17 ], and they depend on the size of one’s muscles [ 18 ]. This difference can cause differences between individuals in neck extension and spinal flexion when walking.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of shoe attrition could be classified into lateral, medial, and central degradation ( Baumfeld et al, 2015 ). Lateral heel degradation was found to be the most popular pattern according to a measurement of over 200 shoes, with an average shoe age of almost a year ( Sole et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%